DEVELOPMENT OF DENTAL AND ORAL HEALTH CARE IN SPECIALISTIC ORTHODONTY DENTAL SERVICES - Wirda Aulia; Diyah Fatmasari; Bedjo Santoso (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: One of the dental and oral health problems experienced by Indonesian society is malocclusion with a prevalence of 80%. The role of the Dental and Oral Therapist (TGM) in orthodontic treatment who collaborates with specialist dentists to correct malocclusion so that it functions well is not yet fully effective because the TGM only implements/chair side assistants in the fourth stage when the TGM should carry out all stages of dental and oral health care . So it is necessary to develop dental and oral health maintenance in specialist orthodontic services. Objective: To produce and analyze the effectiveness of implementing dental and oral health care in specialist orthodontic dentistry services. Research Method: The research method used is Research and Development and Quasy experimental research design Pretest-Posttest group design. The research respondents were TGM at the Muhammadiyah University Semarang dental and oral hospital, TGM intervention 10 people were given model training and controls were given care from Permenkes No.284 of 2006. Data collection techniques in this research were interviews, questionnaires and observation. Validation of expert data was tested using the Intraclass Correlation Coefficient (ICC) while the model test was processed using the Wilcoxon and Mann-Whitney tests. Results: Development of dental and oral health care in specialist orthodontic dentistry services that are relevant as dental and oral health care with expert validation results of 80% and p-value 0.002. The test results stated that the implementation of effective parenting increased TGM knowledge with a p-value of 0.005, TGM attitudes with a p-value of 0.004, and TGM skills with a p-value of 0.004. Conclusion: The application of dental and oral health care in specialist orthodontic services is effective in increasing TGM behavior